Can water professionals do more?. Issue 2 (3rd March 2020) - Rouse, Michael
ABSTRACT: Based on case studies, the author identifies some critical elements for successful water services. The article reviews some policy aspects, namely the need for sustainable cost recovery, that piped supply is the best option in urban areas, and that there is no viable alternative to continuous (24/7) water supply for achieving sustainable services. Although water professionals are justified in having promoted, and in continuing to promote, these policies, they have failed to communicate these critical elements to government decision makers. The author suggests a possible route to correcting this failure.